1999
DOI: 10.1073/pnas.96.1.272
|View full text |Cite|
|
Sign up to set email alerts
|

Systemic biosynthesis of prostacyclin by cyclooxygenase (COX)-2: The human pharmacology of a selective inhibitor of COX-2

Abstract: Prostaglandins (PG) are synthesized by two isoforms of the enzyme PG G/H synthase [cyclooxygenase (COX)]. To examine selectivity of tolerated doses of an inhibitor of the inducible COX-2 in humans, we examined the effects of celecoxib on indices of COX-1-dependent platelet thromboxane (Tx) A 2 and on systemic biosynthesis of prostacyclin in vivo . Volunteers received doses of 100, 400, or 800 mg of celecoxib or 800 mg of a nonselective inhibitor, ibuprofen. Ibupr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

52
760
3
25

Year Published

2000
2000
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,196 publications
(840 citation statements)
references
References 71 publications
(73 reference statements)
52
760
3
25
Order By: Relevance
“…In particular, NSAIDs could have a significant impact on endothelial function. The nonselective NSAIDs inhibit production of both prostacyclin (a vasodilator) and thromboxane A 2 (a vasoconstrictor), whereas the cyclooxygenase-2 (COX-2)-specific inhibitors selectively inhibit prostacyclin alone (39). Fifty-six percent of the RA patients in this study were taking various selective and nonselective NSAIDs, the plasma half-lives of which range from 1.5 to 17 hours.…”
Section: Discussionmentioning
confidence: 94%
“…In particular, NSAIDs could have a significant impact on endothelial function. The nonselective NSAIDs inhibit production of both prostacyclin (a vasodilator) and thromboxane A 2 (a vasoconstrictor), whereas the cyclooxygenase-2 (COX-2)-specific inhibitors selectively inhibit prostacyclin alone (39). Fifty-six percent of the RA patients in this study were taking various selective and nonselective NSAIDs, the plasma half-lives of which range from 1.5 to 17 hours.…”
Section: Discussionmentioning
confidence: 94%
“…As COX-2 is constitutively expressed in the kidney and contributes to renal haemodynamics, 52 the renal safety of COX-2 inhibition using valdecoxib has been questioned. Pooled data on renal safety obtained from osteoarthritis and rheumatoid arthritis trials have demonstrated that the incidence of common renal adverse effects (albuminuria, peripheral oedema and hypertension) following selective COX-2 inhibition with 40 mg of valdecoxib is higher (0.9%, 2.3% and 2.8%, respectively) than that for placebo (0.2%, 0.7% and 0.6%, respectively), but does not significantly exceed that for traditional NSAIDs (0.5%, 2.2% and 1.5%, respectively).…”
Section: Renal Effectsmentioning
confidence: 99%
“…Inhibition of the COX-2 isoform limits the synthesis of inflammatory and algesic mediators as may be released during tissue injury and thereby provides effective analgesia. 1,5,[9][10][11][12][13][20][21][22] However, nonselective NSAIDs have not been uniformly embraced as perioperative analgesics, primarily because of potentially undesirable binding to the COX-1 isoform. Inhibition of this isoform prevents such constitutive physiologic functions as generation of thromboxane (for vasoconstriction and platelet-derived hemostasis) and maintenance of gastrointestinal mucosal integrity.…”
Section: Objectifmentioning
confidence: 99%